PERAN DPD DAN GAGASAN AMANDEMEN KELIMA UUD 1945 - Nuruddin Hady (Jurnal Ilmiah Pendidikan Pancasila dan Kewarganegaraan, 2011)
Regional Representative Council (PRC) is a new state institution based on the third amendment of the Constitution 1945. It is regulated in the Stipulation of Atticle22 C and Article 22D of the Constitution 1945. This institution is the substitute of regional and assembly delegations, as we know before. It is only a weak party; however, it has a quite strong power. Therefore, it emerges criticisms that PRC is no more than a group of staffs who are sub ordinate to the Parliament. As a result, it leads to the idea of the next amendment of the Constitution 1945, particularly on the power of pRC. In the reality, there are many disregarded cases dealing with regional autonomy that should be the attention of PRC. Take, for example, managements of regional finances from public allocation funds. as well as from natural resources of the regions. Other cases are poor nutrition, starving, and floods as the result of bad space managements. These cases get only minor attention from PRC' In this case, pRC is considered insensitive to the issues and developments of the regions. Therefore, the Fifth Amendment needs to be taken into account. However, before we go further' we need to prepare the grand design. There should be clear what are being improved. In the end, the amendment wili not be the process of mending or patching only. Yet, the peoples can take the benefits of it.